Game method application efficiency for speed and power capability development of trampoline athletes at the initial training stage - Дейнеко, Альфія (Slobozhanskyi Herald of Science and Sport, 2017)
Alfia Deineko Purpose: to prove the effectiveness of using the game method for speed and power capability development of trampoline athletes at the initial training stage. Material & Methods: in the article the materials of the research that was carried out with the help of pedagogical testing of trampoliners of 7–8 years on the basis of the Children and Youth Sports School No. 7, Trampoline Department of Kharkov. Results: conducted pedagogical experiment showed the effectiveness of the developed methodology for the development of speed-strength abilities of trampoline athletes at the initial training stage using the game method. Conclusion: results of the experiment confirm the importance of the use of the game method for the development of speed-strength abilities in the initial training of young trampolines, which further affects the level of their technical preparedness and the effectiveness of competition activities.